Pengaruh Jenis Kayu sebagai Bahan Stup terhadap Peningkatan Produktivitas Lebah Trigona sp. - Zulkahfi (Pangale Journal of Forestry and Environment, 2022)
The requirement for trigona honey is increasing, it is causing various study to be carried out to increase the productivity of bees in producing honey. The use of wood species in the manufacture of trigona stup can be one of the factors that affect the development and productivity of trigona bees. The purpose of this study was to determine the effect of wood species as a stup material on increasing the productivity of Trigona sp. The research was conducted in March-June 2022 in Mirring village, Polewali Mandar district. The stup is made using three types of wood, namely jackfruit wood, sengon wood, and white teak wood. Trigona bees were transferred to each stup, then placed at a distance of 2 meters between the stup. Observations and weighing periodically every 10 days for a period of 80 days. The results showed that the manufacture of stup from the three types of wood had a significant effect on increasing the weight of trigona nests and there was a significant difference in the increase in nest weight of stup made of jackfruit wood compared to sengon wood and white teak wood. The increase in nest weight continued for every observation on the stup made of three types of wood.